2021
DOI: 10.1177/13591045211058326
|View full text |Cite
|
Sign up to set email alerts
|

The process, benefits and challenges of providing psychological consultation in adoption services

Abstract: Psychological consultation is one way of reaching a greater number of families with limited resources, yet little is known about the benefits and challenges of this intervention in adoption. We qualitatively explored consultations provided to adoption social workers by clinical psychologists. Six social workers and four clinical psychologists participated in semi-structured interviews. Five themes with supporting sub-themes were identified: (1) A context of highly emotive work with scarce resources; (2) consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, the third author conducted the literature review after the thematic analysis. This meant that the analysis was construed independently from pre-existing literature and more likely to be a reflection of the data collected (Draper et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the third author conducted the literature review after the thematic analysis. This meant that the analysis was construed independently from pre-existing literature and more likely to be a reflection of the data collected (Draper et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This paper adds to the literature by providing support for a distinct systemic model of consultation. Recent research found that consultation fulfilled the need to move skilled mental health providers and therapeutic interventions into community resources, rather than reserving them for specialist services (Draper et al, 2022). The findings of the study align a model of consultation within the development of a broader relationship focused way of working with children, families, schools and other partners to improve children’s mental health as part of a broader community partnership approach (explained in van Roosmalen, 2018).…”
Section: Discussionmentioning
confidence: 99%